How Sweden Deals During Global Economic Crisis? - Octaviani, Melinda; Saputro, Guntur Eko; Navalino, Djoko Andreas (Yayasan Sembilan Pemuda Indonesia, 2023)
European countries are currently experiencing economic shocks. Uncontrollable economic downturn and continuously increase of inflation rate. Sweden as one of the European countries did not feel the impact of the recession significantly. Sweden managed to control its economy because it learned from the previous crisis. Some programs are designed to anticipate bad possibilities that will occur as a result of a crisis. Many studies say that Sweden is a European country that has a good crisis. This study aims to analyze how Sweden is dealing with the ongoing crisis due to the Covid-19 pandemic and Russia's Ukraine war and the series of conflicts that are currently happening in the world which have an impact on the world economy. This research was conducted using qualitative methods that use some data from various credible sources and produce conclusions with appropriate facts. The results of this study found that Sweden has succeeded in suppressing the crisis in its country and maintaining the welfare of its people, although it has not been completely free from the effects of the recession and all the possibilities that will occur in the future.